Flexural Fatigue Life Reliability of Alkali-Activated Slag Concrete Freeze-Thaw Damage in Cold Areas - Bin Chen; Jun Wang (Advances in Materials Science and Engineering)
Studying the application of alkali-activated slag concrete for roads in cold areas is of great significance for promoting and developing green building materials. In this study, the effect of freeze-thaw damage on the flexural fatigue properties of alkali-activated slag concrete was studied and the fatigue life of alkali-activated slag concrete with various degrees of damage after freeze-thaw cycles was studied through a three-point flexural test. The results show that the flexural fatigue life decreases with freeze-thaw cycles from 0 to 150 times. Through a distribution fitting test and K-S test results, the flexural fatigue life followed both the two-parameter and three-parameter Weibull distributions. Between them, the three-parameter Weibull distribution fitting had a higher accuracy and better test results. The results of the reliability analysis show that the curves of alkali-activated slag concrete samples with various degrees of freeze-thaw damage for various failure probabilities have good correlation under different stresses, and the correlation correlations were greater than 0.81. The flexural fatigue life of alkali-activated slag concrete samples with various degrees of freeze-thaw damage was more sensitive to freeze-thaw damage under high stresses. It is suggested that the fatigue design of alkali-activated slag concrete should consider the adverse effects of cold areas, and the reliability should be improved accordingly.